1991
DOI: 10.1007/bf00218669
|View full text |Cite
|
Sign up to set email alerts
|

Antipoliomyelitis immunity status among a population that was regularly vaccinated 11?12 years before

Abstract: A study of poliomyelitis neutralizing antibodies was carried out on 165 samples of blood serum drawn from subjects aged 14-15 years who had completed vaccination with OPV 11 or 12 years ago. Two different methods of incubation of the serum-virus mixtures (1 hour at 37 degrees C; 6 hours at 37 degrees C and then 18 hours at 4 degrees C, respectively) and two different cell lines (RC-37 and Hep-2) for the inoculation of these mixtures were employed. The results were also evaluated in relation to different initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The obser vation that antibody levels may decline over time without a cor responding loss of immunity further supports this hypothesis. 10,11,13,14,[25][26][27][28] Therefore, the proportion of the community with adequate protection against poliomyelitis may be higher than that indicated in the data presented here. Notes: (a) 'Blood taken' refers to children from whom blood was collected for the purposes of polio serology.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The obser vation that antibody levels may decline over time without a cor responding loss of immunity further supports this hypothesis. 10,11,13,14,[25][26][27][28] Therefore, the proportion of the community with adequate protection against poliomyelitis may be higher than that indicated in the data presented here. Notes: (a) 'Blood taken' refers to children from whom blood was collected for the purposes of polio serology.…”
Section: Discussionmentioning
confidence: 55%
“…6,[9][10][11][12][13][14] Herd immunity principles indicate that, for polio, 80-97% of a community needs to be immune for herd immunity to exist 24 (this variance is primarily dependent upon hygiene levels within the community). This knowledge, in conjunction with an Italian study, 12 suggests that detectable antibody at 1:4 or even 1:2 provides immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was demonstrated that a further dose of IPV administrated to subjects, with a history of a complete course of OPV vaccination, and lacking detectable antibodies at the dilution 1:4 10 years after, produced a high response after few days [7].…”
Section: Discussionmentioning
confidence: 99%
“…Several serological investigations were conducted in Italy in recent years to evaluate the persistence of induced immunity after a complete course of four doses of OPV [4][5][6][7]. This study aims to give a contribution to the knowledge of the persistence of humoral protection in a Southern area of Italy, in a population at 5 to over 15 years after the fourth dose of OPV attending the secondary and high school.…”
Section: Introductionmentioning
confidence: 99%